2018
DOI: 10.1007/s10773-018-3784-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Phase Transition from Regular Bardeen Black Hole Surrounded by Quintessence

Abstract: In this paper, thermodynamics and phase transition are investigated for the regular Bardeen black hole. Considering the metric of the Bardeen spacetime, we derived the Unruh-Verlinde temperature. Using the first law of thermodynamics, we derived the expression of the specific heat and plot its behavior. It results that the magnetic monopole charge β reduces the temperature and induces a thermodynamics phase transition in the spacetime. Moreover, when increasing β, the transition point moves to higher entropy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 73 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…The metric for the regular Bardeen AdS black hole surrounded by quintessence is given by [75,[80][81][82],…”
Section: Thermodynamics Of the Black Holementioning
confidence: 99%
See 1 more Smart Citation
“…The metric for the regular Bardeen AdS black hole surrounded by quintessence is given by [75,[80][81][82],…”
Section: Thermodynamics Of the Black Holementioning
confidence: 99%
“…Phase transitions in black holes surrounded by quintessence are widely studied. Thermodynamics of Reissner-Nordström and regular black holes surrounded by quintessence were investigated in [77][78][79][80][81][82][83]. Thermodynamic geometry and geometrothermodynanics for different regular black holes were studied in [65].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more regular black hole models have been established, and the related physical properties have been widely studied. [38][39][40][41][42][43][44][45][46][47][48][49]. Therefore, it is necessary to study the influence of the relevant state parameters on the shadow image and observation characteristics in the Bardeen black hole.…”
Section: Introductionmentioning
confidence: 99%
“…Wei and Liu [29] discussed a relation between phase transition and null geodesics of charged AdS BH. Saleh et al [30] examined thermodynamics as well as phase transition of Bardeen BH surrounded by quintessence and found that presence of quintessence induces phase transition in considered BH. Kuang et al [31] evaluated thermal quantities of AdS non-linear electrodynamic BH.…”
Section: Introductionmentioning
confidence: 99%